Superadded Coinfections and Antibiotic Resistance in the Context of COVID-19: Where do We Stand? - Kayarat, Bhavana (Indian J Crit Care Med, 2021)
PURPOSE OF REVIEW: Poor outcomes in the current coronavirus disease 2019 (COVID-19) pandemic have been attributed to superadded bacterial coinfections. The World Health Organization has reported overzealous usage of broad-spectrum antibiotics during this current pandemic raising concerns of increasing antimicrobial resistance? Therefore, the knowledge of coinfection and the common pathogens during these challenging times is essential for antibiotic stewardship practices. RECENT FINDINGS: The incidence of reported superimposed bacterial and viral coinfections in COVID-19 patients is around 0.04 to 17%. However, more than 70% of patients have received broad-spectrum antibiotics. The presence of a simultaneous coinfection can be suspected in patients with neutrophilic lymphocytosis and elevated procalcitonin in the setting of COVID-19. Multiplex polymerase chain reaction (PCR) panels, with its short turnaround time, aid in the definitive diagnosis of possible coinfection. Acinetobacter baumanii, Mycoplasma pneumonia, influenza virus, Aspergillus, Candida, etc., are commonly implicated pathogens. SUMMARY: Rapid characterization of coinfection and avoidance of overzealous use of broad-spectrum antibiotics in COVID-19 patients are the key to prevent antibiotic resistance during this pandemic. HOW TO CITE THIS ARTICLE: Kayarat B, Khanna P, Sarkar S. Superadded Coinfections and Antibiotic Resistance in the Context of COVID-19: Where do We Stand? Indian J Crit Care Med 2021;25(6):699–703.